2019
DOI: 10.1073/pnas.1902688116
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution contrast-enhanced microCT reveals the true three-dimensional morphology of the murine placenta

Abstract: Genetic engineering of the mouse genome identified many genes that are essential for embryogenesis. Remarkably, the prevalence of concomitant placental defects in embryonic lethal mutants is highly underestimated and indicates the importance of detailed placental analysis when phenotyping new individual gene knockouts. Here we introduce high-resolution contrast-enhanced microfocus computed tomography (CE-CT) as a nondestructive, high-throughput technique to evaluate the 3D placental morphology. Using a contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…Fetus position within the uterine horn in rodent animal models has been described as an important factor in feto-placental development [34] and the variation in fetal weight per conceptus in our mouse model further supports the rational that each fetus with its respective placenta is biologically distinct. Additionally, it has recently been suggested that dimorphisms, e.g., placental and fetal sex, exist which have an impact on placental development and fetal growth [35,36]. Furthermore, when collecting physiological data from embryos in utero or investigating feto-placental units in genetically modified dams, differences between each feto-placental unit can be observed regarding heart rate [37] or normal fetal development independent of fetal genotype [38], respectively, suggesting that analyzing multiple placentas per dam could be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Fetus position within the uterine horn in rodent animal models has been described as an important factor in feto-placental development [34] and the variation in fetal weight per conceptus in our mouse model further supports the rational that each fetus with its respective placenta is biologically distinct. Additionally, it has recently been suggested that dimorphisms, e.g., placental and fetal sex, exist which have an impact on placental development and fetal growth [35,36]. Furthermore, when collecting physiological data from embryos in utero or investigating feto-placental units in genetically modified dams, differences between each feto-placental unit can be observed regarding heart rate [37] or normal fetal development independent of fetal genotype [38], respectively, suggesting that analyzing multiple placentas per dam could be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…, 1200 projections of exposure time with a flat panel CMOS detector with Gadox-scintillator, PerkinElmer, USA) (Bartels et al, 2013). Metal-staining (here UA) of the lung tissue helped to achieve sufficient contrast, similar to previous CT-studies of other biological tissues (Müller et al, 2017;Busse et al, 2018;De Clercq et al, 2019). The resulting overview scans could also be correlated well with histological sections.…”
Section: Additional Informationmentioning
confidence: 61%
“…Although the mechanism by which the phenotype of the Skp2 −/− mouse placenta is influenced by genetic background is unclear, one possibility is that mice on the C57BL/6 background are more susceptible to the development of placental defects. Placental morphology differs between the C57BL/6‐ and 129/SvJ‐inbred strains (De Clercq et al., 2019; Tunster, Pette, & John, 2012). Placental volume of C57BL/6 mice is larger than that of 129/SvJ mice, although fetal weight is similar in the two strains.…”
Section: Discussionmentioning
confidence: 99%